HUBUNGAN PERILAKU PEMANFAATAN PROLANIS DENGAN STATUS KESEHATAN PASIEN DIABETES MELLITUS DI KOTA PURWOKERTO - anugrah dea (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2017)
Background : Diabetes Mellitus is a metabolic disease characterized by chronic hyperglycemia caused by insulin resistance and or the effects of insulin secretion. Diabetes Mellitus can not be cured, but blood sugar levels can be controlled. PROLANIS is a chronic disease management program for chronically ill patients who aims to encourage chronic disease patients to achieve optimum quality of life against patients with Type II DM and Hypertension so as to prevent the occurrence of disease complications. The purpose of this study was to determine the relationship of PROLANIS use with the health status of Diabetes Mellitus patients. Methods : This research is an analytic research with cross sectional study design. Sample amounted to 191 people with sampling technique Purposive Sampling. The data collected in this study came from secondary data including a list of prolanis participants, a list of attendees of each prolanis activity, and data on blood pressure and blood glucose examination. Results : Based on the results of research, obtained patients who have good health status 42 people (78,0%). Participation of participants in good proanic gymnastics activity 128 patients (67,0%). While health education activity pasrtisipasi good 128 patient (67,0%). Chi Square test results were significant 0.018 (p <0.05), which means that there is a relationship between prolanic exercise with health status of Diabetes Mellitus patients. Conclusion : There is a relationship between prolanic gymnastics and the health status of Diabetes Mellitus patients. Keyword : Prolanis, Health Status, Diabetes Mellitus